Making sense of an historic landscape - Rippon, Stephen 1968- (Oxford Univ. Press, 2012)
This volume explores how the archaeologist or historian can understand variations in landscapes. Making use of a wide range of sources and techniques, including archaeological material, documentary sources, and maps, Rippon illustrates how local and regional variations in the 'historic landscape' can be understood.
Published to Oxford Scholarship Online: March 2015
Keywords: Geschichte; Siedlungsstruktur; Landnutzung; Ländlicher Raum; England